2018
DOI: 10.1590/0037-8682-0279-2017
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of first-wave protease inhibitors in hepatitis C virus genotype 1 infection: a multicenter study in Brazil

Abstract: Introduction: In 2013, combination therapy using peginterferon, ribavirin, and boceprevir or telaprevir was introduced to treat hepatitis C virus genotype 1 infection in Brazil. The effectiveness of this therapy in four Brazilian regions was evaluated. Methods: Clinical and virological data were obtained from patients of public health institutions in five cities, including sustained virological response (SVR) and side effects. Patients with advanced fibrosis (F3/4), moderate fibrosis (F2) for > 3 years, or ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
1
0
3
Order By: Relevance
“…Despite the limitations, this work is relevant for analyzing the incorporation of drugs associated with high costs into a public health system. The effectiveness data of this and other phase IV studies indicated that premarketing trials overestimated the effectiveness of TT 19,20,21,34 .…”
Section: Nmb: Net Monetary Benefitsmentioning
confidence: 64%
“…Despite the limitations, this work is relevant for analyzing the incorporation of drugs associated with high costs into a public health system. The effectiveness data of this and other phase IV studies indicated that premarketing trials overestimated the effectiveness of TT 19,20,21,34 .…”
Section: Nmb: Net Monetary Benefitsmentioning
confidence: 64%
“…Foi possível verificar a presença de efeitos colaterais na maioria dos pacientes, sendo os principais sintomas: astenia, dor abdominal, mialgia e prurido. Apesar de melhores resultados, os inibidores de protease apresentavam ainda baixas taxas de RVS, tratamento prolongado e com muitos efeitos colaterais, fatores que somados contribuíam para uma baixa eficácia do esquema empregado (LOBATO et al, 2018;NICACIO et al,.2019).…”
Section: Dignóstico E Monitoramentounclassified
“…Verificou-se taxa de RVS média de 56,6% (51,9% para BOC e 58% para TVR) e reações adversas severas ocorreram em 44,2% dos pacientes, com seis mortes registradas(CALLEFI et al, 2017). Em outro estudo multicêntrico brasileiro, realizado por Lobato e colaboradores, encontrou-se taxa global de RVS de 54,2% e observou-se ocorrência de reações adversas em 87,5% dos pacientes(LOBATO et. al., 2018).…”
unclassified
“…al., 2018). Em estudo realizado no Hospital das Clínicas da Faculdade de Medicina de Ribeirão Preto, com uma amostra de 115 pacientes que receberam terapia tripla, 61,7% alcançaram RVS (58,3% para BOC e 62,1% para TVR) (RODRIGUES, 2017).Além das taxas de RVS insatisfatórias encontradas e da elevada incidência de reações adversas, a terapia com os IPs de primeira geração apresentava um alto custo e esquemas posológicos complicados, onde tanto BOC quanto TVR deveriam ser administrados diversas vezes ao dia e sua absorção no trato gastrointestinal dependia da quantidade de alimentos gordurosos ingeridos concomitantemente, fatores que dificultavam a adesão ao tratamento(LOBATO et. al., 2018).…”
unclassified